Analysis of the YouTube Videos About Children with Cerebral Palsy: a research article - Fidan, Öznur; Çakırlı, Merve; Dertli, Semiha; Çolak, Ertuğrul (Ümit Muhammet KOÇYİĞİT, 2024)
Analysis of the YouTube Videos About Children with Cerebral Palsy: a research article ABSTRACT Purpose: Because cerebral palsy (CP) is a long-term disease, parents need to have information at hand throughout their lives. The videos shown on YouTube, may be inadequate or contain erroneous information since they are not subjected to a process of evaluation and are not regularly updated. In this study, we investigated the scientific content and quality of the YouTube videos related to CP. Material and Methods: The YouTube online library was searched using the term “Children with Cerebral Palsy”. The quality and content of the videos was explored with the GQS (Global Quality Scale) and scientific content with the CPss (Cerebral Palsy Scoring System). The characteristics of the videos (video length, source, date of upload, likes etc.) were recorded. Results: The study was completed with 29 videos. Of the videos, 43.44% included diagnostic information, while 23.3% contained treatment-related information, and 21.18% provided information about associated comorbidities. The mean GQS score was 1.96 ±1.34, the CPss score was 5.75±4.08. According to the quality level of the information content, only 1 video qualified as providing good, 7 videos as moderate, and 21 videos as providing poor information. Conclusion: Health professionals need to be aware of the content available on video-sharing platforms and should be ready to direct their patients to e-information sources that provide accurate and reliable information. Keywords: Cerebral Palsy; children; YouTube; video; quality
Keywords: Rehabilitation; Rehabilitasyon